A new Dichotrachelus Stierlin from Val Grande (Piemonte, Italy) (Coleoptera, Curculionidae) with comments on biogeography and evolution of high alpine species of the genus - Alexander Szallies; Christoph Germann (Alpine Entomology)
Dichotrachelus sonjae sp. nov. was discovered in a cold north-exposed scree slope in the Togano ridge area in Piemonte North of Val Grande. It is described and compared with the most similar species. Based on morphology and molecular data presented here, Dichotrachelus lepontinus Osella, 1971, distributed from Piemonte in Italy (Monte Rosa) eastwards to the Misox mountains of Switzerland, is its sister species. Dichotrachelus meregallii Osella, 1971 is another closely related species. Phylogeographic and biogeographical considerations on the development of that particularly lithophilous and high alpine living group of Dichotrachelus are presented.